2016
DOI: 10.1161/circresaha.116.306531
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of Saying NO

Abstract: T he historical demonstration by Furchgott and Zawadzki 1 that removal of the endothelium abrogates the in vitro vasodilator effect of acetylcholine has led to the identification 30 years ago of nitric oxide (NO) as a major endogenous local regulator of vascular tone. [2][3][4][5][6][7][8][9][10] When the ability of endothelial cells to produce NO is blunted, the ensuing vascular dysfunction sets the stage for the occurrence of cardiovascular disease in general, and atherosclerosis in particular. [11][12][13][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(187 citation statements)
references
References 191 publications
(393 reference statements)
11
156
0
Order By: Relevance
“…In males, we showed that obesity and hyperlipidemia profoundly impaired NO availability in mesenteric resistance microvessels. This is consistent with many prior studies demonstrating that vascular NO bioavailability is impaired by obesity and metabolic syndrome; however, much of the data supporting this concept were performed only in males, thereby missing potential sex‐specific mechanisms (reviewed in 7, 40). In addition, many such studies, regardless of sex, measured endothelial responses in the mouse aorta,27, 30 a conduit vessel that is larger and thus easier to study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In males, we showed that obesity and hyperlipidemia profoundly impaired NO availability in mesenteric resistance microvessels. This is consistent with many prior studies demonstrating that vascular NO bioavailability is impaired by obesity and metabolic syndrome; however, much of the data supporting this concept were performed only in males, thereby missing potential sex‐specific mechanisms (reviewed in 7, 40). In addition, many such studies, regardless of sex, measured endothelial responses in the mouse aorta,27, 30 a conduit vessel that is larger and thus easier to study.…”
Section: Discussionsupporting
confidence: 89%
“…Because estrogen has been shown to transcriptionally regulate SK3 and IK1 expression,15, 51 the decrease in estradiol levels in females exposed to hyperlipidemia could contribute to the reduced expression of endothelial potassium channels and impaired endothelial function. Estrogen is also known to enhance endothelial NO production by activating eNOS via phosphorylation (reviewed in 40). In this study, however, exposure to cardiometabolic risk factors did not change eNOS phosphorylation in mesenteric vessels in either sex.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13 Through various intrinsic mechanisms, endothelial cells are normally in a state which suppresses proinflammatory gene expression, recruitment of monocytes, and development of atherosclerosis. 1416 …”
Section: Part I Cerebrovascular Disease: the Prelude To Strokementioning
confidence: 99%
“…It has to be noticed that global endothelial dysfunction in SHR not only involves decreased NO bioavailability but also decreased production of endothelium-hyperpolarizing factor and prostacyclin (Deanfield et al, 2005; Schini-Kerth et al, 2011), higher production of endothelium-dependent vasoconstrictive agents (Touyz and Schiffrin, 2004; Félétou et al, 2009) and possible long term structural changes (Touyz and Schiffrin, 2004; Lee and Griendling, 2008). For other cardiovascular diseases, such as atherosclerosis, the prominent feature for endothelial dysfunction lies on the reduction in NO bioavailability, which is regarded as a major factor in the pathogenesis of the disease (Mudau et al, 2012; Jensen and Mehta, 2016; Vanhoutte et al, 2016). …”
Section: Discussionmentioning
confidence: 99%